2021
DOI: 10.3390/pathogens10020177
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Laboratory Diagnosis—Lessons Learned from Recent Animal Trials

Abstract: African swine fever virus (ASFV) causes a hemorrhagic disease in pigs with high socio-economic consequences. To lower the impact of disease incursions, early detection is crucial. In the context of experimental animal trials, we evaluated diagnostic workflows for a high sample throughput in active surveillance, alternative sample matrices for passive surveillance, and lateral flow devices (LFD) for rapid testing. We could demonstrate that EDTA blood is significantly better suited for early ASFV detection than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 47 publications
6
32
2
Order By: Relevance
“…Of those samples derived from animal trials (n=64), 56 were true positive according to the rapid test, resulting in a sensitivity of 87.5% in that group. This goes along with observations in a previous study performed in our group, when the LFA was most sensitive during the clinical phase of ASF, at the peak of viral replication (Pikalo et al, 2021). In the present study, however, it was observed that the influences of clotting and decay in the carcass-derived samples seemed be able to outweigh the effects of higher viral loads, since here no clear correlation even with very low cq values and positive results in the LFA were observed (see supporting table 2).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Of those samples derived from animal trials (n=64), 56 were true positive according to the rapid test, resulting in a sensitivity of 87.5% in that group. This goes along with observations in a previous study performed in our group, when the LFA was most sensitive during the clinical phase of ASF, at the peak of viral replication (Pikalo et al, 2021). In the present study, however, it was observed that the influences of clotting and decay in the carcass-derived samples seemed be able to outweigh the effects of higher viral loads, since here no clear correlation even with very low cq values and positive results in the LFA were observed (see supporting table 2).…”
Section: Resultssupporting
confidence: 91%
“…The increase of overall positive results is in accordance with the sensitivity of 48.75% we observed in all of the previously freeze-thawed carcass-derived samples (C1-C80), where 39 positives were detected by the LFA (see supporting table 2). Interestingly, however, we did not observe a better sensitivity after freeze-thawing in EDTA-blood samples of high quality in a previous study by our group (Pikalo et al, 2021). The positive effect of freeze-thawing is probably due to the fact that most of the virus in blood is associated with erythrocytes (Wardley & Wilkinson, 1977), and therefore, the destruction of blood cells during freeze-thawing results in a higher antigen availability for detection in the test, a process especially effective when erythrocytes are bound to clots in samples of reduced quality.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…They are commercially available, but lack sensitivity [181,215]. The same is true for antigen lateral flow assays, which showed some promising results in experimental settings [182,216], but would failed to detect most confirmed ASF cases from Germany (P. Deutschmann, personal communication).…”
Section: Detection Of Asf Virus Asfv Antigen and Genomementioning
confidence: 99%
“…In general, reliable tools for the direct (pathogen) and indirect (antibody) diagnosis of ASF exist that work with appropriate samples from both domestic pigs and wild boar [ 181 ]. There is no difference in test performance or the suitability of matrices when testing high-quality samples from either domestic pigs or wild boar as depicted in Figure 3 [ 182 ].…”
Section: Diagnosis Of Asf In Wild Boarmentioning
confidence: 99%